The Influence of Agriculture, Fisheries and Tourism Sectors on Local Own-Source Revenue and Labor Absorption - Haryady, Haryady; Suharto, Rahcmad Budi; Lestari, Diana (Research Horizon, 2026)
This study examines the government’s strategy to lessen reliance on capital-intensive manufacturing by strengthening agriculture, fisheries, and tourism as key sectors for boosting Local Own-Source Revenue and employment. The purpose of this study is to analyze the influence of the agricultural, fisheries, and tourism sectors on local own-source revenue and labor absorption in Bontang City. The study applies a quantitative causal-associative design using path analysis and relying on secondary data from the central statistics agency, the agriculture, fisheries, and tourism departments, and the regional financial management agency of Bontang City for the 2020–2024 period. The findings reveal that all three sectors have a positive and significant effect on local own-source revenue, with the tourism sector contributing the most, followed by the agricultural and fisheries sectors. Meanwhile, in terms of labor absorption, the agricultural sector has the most dominant influence compared to the other two sectors. The three sectors significantly contribute to the improvement of local own-source revenue and labor absorption. The study concludes that cross-sectoral synergy among labor-intensive sectors can strengthen local economic resilience and support sustainable regional economic growth. The implication is that local governments should enhance inter-agency collaboration, expand public investment, and formulate community-based economic empowerment policies rooted in local resources.